Draft Sikkim Ninth Five Year Plan 1997-2002 Volume-I - Planning Commission (Planning Commission, 1997)
Sikkim is a tiny hilly State ensconced in the North Eastern Himalayas where approximately share of 0.05 percent of the total population of the country reside. Sikkim became the 22nd State of India only in 1975. the third highest mountain in the world Mount. Kanchenzonga which is venerated by the Sikkimese as their guardian deity lies on its North West corner. the share of the State in the country's geographical area is only 0.22%. With an area of 7096 sq.km, measuring approximately 113 kms. from North to South and 64 kms. from East to West, Sikkim has an elevation range from 440 metres to over 8540 metres above the sea level.
Planning and Development Department, Govt of Sikkim